2014
DOI: 10.1002/ps.3753
|View full text |Cite
|
Sign up to set email alerts
|

Mutations at codon position 1999 of acetyl‐CoA carboxylase confer resistance to ACCase‐inhibiting herbicides in Japanese foxtail (Alopecurus japonicus)

Abstract: This study revealed that A. japonicus had multiple copies of genes encoding plastidic ACCase, and each gene was able to carry its own mutation. It also established the clear importance of the W1999C and W1999L mutations in conferring resistance to ACCase-inhibiting herbicides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 38 publications
1
61
0
1
Order By: Relevance
“…), Japanese foxtail ( Alopecurus japonicus Steud. ), keng stiffgrass ( Pseudosclerochloa kengiana (Ohwi) Tzvel. ), and hexaploid A. fatua .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…), Japanese foxtail ( Alopecurus japonicus Steud. ), keng stiffgrass ( Pseudosclerochloa kengiana (Ohwi) Tzvel. ), and hexaploid A. fatua .…”
Section: Discussionmentioning
confidence: 99%
“…We further found that all resistant plants ( n ≥ 50) carrying the Trp‐1999‐Ser mutation were heterozygous using the dCAPS genotyping. Similarly, when studying the mutation(s) of ACCase in the tetraploid P. kengiana and A. japonicus and hexaploid A. fatua , no homozygous‐resistant genotype was detected using dCAPS markers. This could be explained by the primers used for dCAPS amplifying the same region of multiple ACCase alleles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In China, sustained reliance on ACCase and/or ALS inhibitors to control weeds has led to the evolution of many resistant populations resulting from mutant ALS and ACCase [16,20]. In the JTJY-1 population, the presence of two different TSR mechanisms (ALS and ACCase mutations) in individual plants has appeared.…”
Section: Discussionmentioning
confidence: 99%
“…Three sets of primers (Table 3) spanning all eight known mutation sites affecting ALS efficacy based on Alopecurus myosuroides (AJ437300) sequence available in GenBank, were designed using the Primer Premier 5.0 software, and two primers (Table 3) previously used in a study by Xu et al [16] were used to amplify and sequence ACCase gene fragments of A. aequalis.…”
Section: Gene Sequencingmentioning
confidence: 99%